Status of Basement Terranes in Orogens: Insights From the Cadomian Domain of the North Armorican Variscides, Western France. Issue 5 (25th May 2021) - Le Gall, Bernard; Authemayou, Christine; Graindorge, David; Duperret, Anne; Kaci, Tassadit; Ehrhold, Axel; Schmitt, Thierry
Abstract: The stable versus mobile behavior of basement terranes in orogens is discussed about the North Armorican Cadomian‐floored domain (NAD) in the Armorican Variscides, Western France. Our onshore/offshore structural study demonstrates the heterogeneous nature of the NAD which comprises: (a) a southern part which remained stable during both the Paleozoic extensional and compressional (Variscan) events and (b) a northern part which was initially the locus of extensive Paleozoic sedimentary basins before recording Variscan deformation. Our work supplies a more complete structural picture of the Variscan pattern in Northern Armorica as a whole: (a) as precising the spatial distribution of Variscan strain, (b) as emphasizing its importance with a bulk shortening estimated at 30% in the North Cotentin fold‐and‐thrust belt, and (c) as regarding a newly identified pattern of sinistral ductile shear zones in the Morlaix area as lateral ramps that parallel the western edge of the rigid (southern) Cadomian block in a indenter kinematic setting. At a wider scale, compiling structural data set from others Cadomian terranes in the Variscan belt of Central (Bohemia) and Western (Iberia) Europe leads us to hypothetize that their stability versus reworking during the Variscan orogeny relies primarily on the mechanical/thermal state of their lithosphere at the end of the Paleozoic extensional stage. Key Points: The North Armorican Cadomian domain comprises a northern part with Variscan overprint, and a southern stable and rigid part Variscan reworking of Cadomian terranes in the Central and Western European Variscides, occurred in portions of lithosphere which were previously stretched Our structural study is based on an onshore/offshore approach combining high‐resolution bathymetric records and field investigations